Research perspective in the clinical management of Kawasaki disease - Yi, Xiong-xiong; Zhang, Wen-rong; Wang, Dong-mei; Wang, Xiu-ping; Zhang, Fen-xia (Frontiers in Pediatrics, 2024)
This study examines research progress in the clinical diagnosis, treatment, and prevention of cardiovascular complications in Kawasaki Disease (KD). Starting with an overview of the disease, it introduces KD's clinical manifestations, etiology, epidemiological features, and its impact on the cardiovascular system. Subsequently, the study discusses in detail the diagnostic methods, pathological mechanisms, and treatment strategies for KD, including foundational and emerging approaches such as high-dose intravenous immunoglobulin and aspirin therapy, biologic therapy, and corticosteroid pulse therapy. Additionally, it outlines strategies for preventing cardiovascular complications, including early risk assessment and long-term management. The study also explores the intersection of the COVID-19 pandemic with an increase in KD-like symptoms, emphasizing the need for further studies on the association between SARS-CoV-2 and KD. Lastly, it explores future research directions to enhance understanding of KD and improve patient outcomes and quality of life. This study provides valuable insights into the comprehensive treatment and management of KD and highlights avenues for future research.